2008
DOI: 10.1097/bpb.0b013e32830b61f4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of type II tibial intercondylar eminence fractures in children

Abstract: The objective of this study was the evaluation of the therapeutic options in type II tibial intercondylar eminence fractures. Seventeen children were treated surgically. Open reduction, curettage of the fracture area and internal fixation were performed. The average follow-up was 3 years. No reduction in sport activities or instability have been noted. The average Lysholm score was 99.7 at the latest follow-up. We recommend the surgical procedure for type II tibial intercondylar eminence fractures in children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 27 publications
0
35
0
2
Order By: Relevance
“…This does not represent the true incidence of the different types in the population, as inclusion criteria for several studies only included type II and III tibial eminence fractures. Most type IV fractures were included with type III fractures; ten papers included the Zarincznyj modification separately [2, 15, 18, 20, 21, 27, 31, 33, 35, 40]. …”
Section: Resultsmentioning
confidence: 99%
“…This does not represent the true incidence of the different types in the population, as inclusion criteria for several studies only included type II and III tibial eminence fractures. Most type IV fractures were included with type III fractures; ten papers included the Zarincznyj modification separately [2, 15, 18, 20, 21, 27, 31, 33, 35, 40]. …”
Section: Resultsmentioning
confidence: 99%
“…Although many successful arthroscopic reduction and internal fixation (ARIF) techniques using a variety of fixation methods have been described in the literature, fixation is most commonly achieved with pull-out sutures or with screws [2,8,12,13,16,17,19,27,28,31,36,44]. However, the screw fixation and the pull-out suture fixation with nonabsorbable sutures have several limitations [7,14,21,42,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Fixation can be performed with sutures [77][78][79][80][81], (Fig. 5) metal screws [82][83][84][85], bioabsorbable nails [86], Kirschner wires [36,41,43,76], or suture anchors [87,88]. Several reports have found that screws can actually weaken the small fragment or cause comminution [78] and thus recommend suture fixation, which has demonstrated similar or improved strength profiles [89][90][91].…”
Section: Tibial Eminence Fracturementioning
confidence: 99%